Impact of (68)Ga-DOTA-Peptide PET/CT on the Management of Gastrointestinal Neuroendocrine Tumour (GI-NET): Malaysian National Referral Centre Experience - Tan, Teik Hin (Nucl Med Mol Imaging, 2017)
PURPOSE: The National Cancer Institute is the only referral centre in Malaysia that provides (68)Ga-DOTA-peptide imaging. The purpose of this study is to determine the impact of (68)Ga-DOTA-peptide PET/CT on the management of gastrointestinal neuroendocrine tumours (GI-NET). MATERIALS AND METHODS: A cross-sectional study was performed to review the impact of (68)Ga-DOTA-peptide ((68)Ga-DOTATATE or (68)Ga-DOTATOC) PET/CT on patients with biopsy-proven GI-NET between January 2011 and December 2015. Suspected NET was excluded. Demographic data, tumoral characteristics, change of disease stage, pre-PET intended management and post-PET management were evaluated. RESULTS: Over a 5-year period, 82 studies of (68)Ga-DOTA-peptide PET/CT were performed on 44 GI-NET patients. The most common primary site was the rectum (50.0%) followed by the small bowel, stomach and colon. Using WHO 2010 grading, 40.9% of patients had low-grade (G1) tumour, 22.7% intermediate (G2) and 4.5% high (G3). Of ten patients scheduled for pre-operative staging, (68)Ga-DOTA-peptide PET/CT only led to therapeutic change in three patients. Furthermore, false-negative results of (68)Ga-DOTA-peptide PET/CT were reported in one patient after surgical confirmation. However, therapeutic changes were seen in 20/36 patients (55.6%) scheduled for post-surgical restaging or assessment of somatostatin analogue (SSA) eligibility. When (68)Ga-DOTA-peptide PET/CT was used for monitoring disease progress during systemic treatment (sandostatin, chemotherapy, everolimus and PRRT) in metastatic disease, impact on management modification was seen in 19/36 patients (52.8%), of which 84.2% had inter-modality change (switch to everolimus, chemotherapy or PRRT) and 15.8% had intra-modality change (increased SSA dosage). CONCLUSIONS: (68)Ga-DOTA-peptide PET/CT has a significant impact on management decisions in GI-NET patients as it can provide additional information on occult metastasis/equivocal lesions and supply the clinician an opportunity to select patients for targeted therapy.